Internationalization Strategies in Sea Transportation Management: Cross-Border Operations, Global Supply Chain Dynamics, and Comparative Shipping Practices - Naomi Louhenapessy (Global Research Collaboration, 2026)
The sea transportation sector serves as a vital pillar for facilitating global trade, yet the internationalization strategies employed by shipping companies to expand and manage cross-border operations are often underexplored, particularly in the face of contemporary challenges such as regulatory divergence, sustainability requirements, digital transformation, and shifting geopolitical landscapes. This study provides a comprehensive analysis of the internationalization strategies within sea transportation management, focusing on global supply chain dynamics, comparative operational practices across different geographical and institutional settings, and the governance structures that support effective cross-border maritime operations. Through a qualitative research approach that combines thematic analysis, cross-group comparison, and narrative synthesis, the study utilizes expert interviews and document analysis, drawing insights from international shipping strategists, cross-border logistics professionals, maritime regulatory authorities, and academic researchers. The findings highlight four key themes: the multi-faceted nature of maritime internationalization, including market entry, network growth, and institutional adaptation; the critical importance of regulatory compliance and alignment in facilitating smooth cross-border operations; the integration of sustainability principles within international supply chain management; and the organizational capabilities necessary for managing the diverse cultural, institutional, and operational complexities of global maritime networks. This research contributes a unified internationalization framework that links strategic positioning, regulatory alignment, sustainability, and organizational capacity, offering both theoretical advancements for international business and practical guidance for maritime organizations navigating cross-border challenges.